NiTi / Al-based composite material with double-heterogeneous structure as well as preparation method and application of NiTi / Al-based composite material

Through high-energy ball milling and low-temperature sintering hot extrusion processes, NiTi/Al matrix composite materials with bi-isomerial structures were prepared, which solved the problem of difficult to take into account the strength and toughness of existing materials, and achieved the improvement of high tensile strength and elongation. , significantly improves the strength and toughness of composite materials.

CN119220839AActive Publication Date: 2024-12-31HARBIN INST OF TECH
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411338839.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-31
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

Existing NiTi/Al composite materials are difficult to take into account both strength and toughness, especially when manufacturing tripeak grain structures, there is a problem of grain distribution of uneven sizes, which affects its strain hardening and strength-ductility synergistic effect.

Method used

NiTi microparticles with aluminum powder or aluminum alloy powder are subjected to high-energy ball milling to form mixed powders of different sizes, and low-temperature discharge plasma sintering and low-temperature hot extrusion under vacuum conditions to prepare NiTi with bi-isomerial structure/ Al-based composite material forms a brick-like structure with high-density granular hard zone and particle-free tough zone.

Benefits of technology

The tensile strength and elongation of NiTi/Al matrix composite materials have been significantly improved, and the strength and toughness are improved, and the purpose of improving the strength and toughness of the composite materials has been achieved through geometrically necessary dislocations.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220839A_ABST
    Figure CN119220839A_ABST
Patent Text Reader

Abstract

The invention discloses a NiTi / Al-based composite material with a double-heterogeneous structure as well as a preparation method and application of the NiTi / Al-based composite material. The invention belongs to the field of NiTi / Al-based composite materials. The invention aims to solve the technical problem that the strength and toughness of the existing NiTip / Al composite material cannot be considered at the same time. The method comprises the following steps: firstly, mixing NiTip and pure aluminum powder by high-energy ball milling; then NiTip and aluminum alloy powder are subjected to high-energy ball milling and mixing; packaging the two kinds of mixed powder and non-ball-milled aluminum powder in a mold in a layered manner; and finally, performing SPS sintering and low-temperature hot extrusion. According to the prepared double-heterogeneous structure material, different crystal region isomerism is formed in a hard region with high-density particles and a tough region without particles in a matrix, and brick layered structure isomerism is formed in a stacking mode. The method disclosed by the invention can also be used for preparing other NiTi / reinforced metal matrix composite materials. The obtained composite material has high strength and toughness, and is applied to the fields of aerospace and automotive engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of NiTi / Al-based composite materials, and in particular relates to a NiTi / Al-based composite material with a dual-isomeric structure and a preparation method and application thereof. Background Art

[0002] Heterogeneous structure (HS) materials have become an emerging class of materials with excellent properties that cannot be achieved by traditional homogeneous materials. Generally speaking, HS materials consist of ductile and hard zones with significantly different flow stresses. This leads to strain distribution, with the ductile zone carrying a larger strain ratio than the hard zone. Strain gradients will develop near the zone interface to accommodate the strain distribution, which needs to be accommodated by geometrically necessary dislocations (GNDs), resulting in heterogeneous deformation induced (HDI) work hardening and HDI stress strengthening. One feasible strategy is to adjust the grain shape to form matrix heterogeneity based on traditional uniform equiaxed grains. Another feasible way to establish a heterogeneous grain structure is to improve ductility. However, the improvement effect is not obvious.

[0003] In recent years, a trimodal grain structure with grain sizes ranging from nanometers to micrometers has been shown to exhibit better strain hardening and strength-ductility synergy than a bimodal grain structure. However, it is a huge challenge to manufacture metals with a trimodal grain structure. The most commonly used method is to partially recrystallize by annealing after severe plastic deformation, but this method produces an uneven distribution of large and small grains and does not have a toughening effect. Especially for NiTip / Al composites, the uniform dispersion of NiTip, structural integrity and NiTip / Al interface reaction must be considered. Therefore, it is particularly necessary to develop a high-strength and tough NiTip / Al composite material. Summary of the invention

[0004] The purpose of the present invention is to solve the technical problem that the existing NiTip / Al composite material cannot take both strength and toughness into consideration, and to provide a NiTi / Al-based composite material with a dual isomerization structure and a preparation method and application thereof.

[0005] The technical solution of the present invention is as follows:

[0006] One of the objects of the present invention is to provide a method for preparing a NiTi / Al-based composite material having a dual isomerization structure, the method being carried out according to the following steps:

[0007] S1: Mix NiTip (NiTi micron particles) and aluminum powder by high-energy ball milling to obtain NiTip-Al mixed powder;

[0008] S2: mixing NiTip (NiTi micron particles) and aluminum alloy powder by high-energy ball milling to obtain NiTip-Al alloy mixed powder;

[0009] S3: NiTip-Al mixed powder, NiTip-Al alloy mixed powder and unmilled aluminum powder are stacked and packaged in a mold, and low-temperature discharge plasma sintering is performed under vacuum conditions, followed by low-temperature hot extrusion to obtain a NiTi / Al-based composite material with a dual heterogeneous structure.

[0010] It is further defined that the amount of NiTip added in S1 is 11 to 50 wt.% of the pure aluminum powder.

[0011] It is further defined that the high energy ball milling speed in S1 is 300-450 rpm and the time is 8-15 h.

[0012] It is further defined that the particle size of the NiTi-Al mixed powder in S1 is <5 μm.

[0013] It is further defined that the amount of NiTip added in S2 is 11 to 50 wt. % of the aluminum alloy powder.

[0014] It is further defined that the speed of high energy ball milling in S2 is 300-450 rpm and the time is 8-15 h.

[0015] It is further defined that the particle size of the NiTip-Al alloy mixed powder in S2 is 5 to 20 μm.

[0016] It is further defined that the mass ratio of the NiTip-Al mixed powder, the NiTip-Al alloy mixed powder and the unmilled aluminum powder in S3 is (1.5-2.5):(1.5-2.5):1.

[0017] It is further defined that the particle size of the unmilled aluminum powder in S3 is 50 to 150 μm.

[0018] It is further defined that the temperature of the low-temperature discharge plasma sintering in S3 is 500-530° C., the pressure is 40-60 MPa, and the time is 5-15 min.

[0019] It is further defined that the hot extrusion temperature in S3 is 400-430° C., the extrusion ratio is (16-25):1, and the extrusion rate is 0.1-0.5 mm / s.

[0020] The second object of the present invention is to provide a high-strength and tough NiTi / Al-based composite material prepared by the above method, wherein the composite material has a tensile strength of ≥360 GPa and an elongation of ≥6.7%.

[0021] The third object of the present invention is to provide a high-strength and tough NiTi / Al-based composite material prepared by the above method for use in the fields of aerospace and automotive engineering.

[0022] A fourth object of the present invention is to provide an application of the above method in preparing NiTi / metal matrix composite materials.

[0023] It is further defined that the metal matrix is ​​one of Mg, Fe, Ti, Cu and their respective alloys.

[0024] Compared with the prior art, the present invention has the following advantages:

[0025] The dual heterogeneous structural material prepared by the present invention forms different crystal region heterogeneities in the hard area of ​​high-density particles and the tough area without particles in the matrix, and forms brick-laying layered structural heterogeneities in a stacking manner, which brings some special structural effects to the composite material. First, NiTip is mixed with different aluminum matrices. Due to the large difference in hardness of the aluminum matrix, mixed powders of different sizes will be formed when mixed with NiTip using the same process, and then the mixed powders of different sizes are stacked and placed in a reasonable proportion for mixing. Secondly, SPS sintering is combined with low-temperature hot extrusion to adjust the preparation process parameters to prepare NiTip / Al composite materials without interface reaction layers, which significantly improves the strength and toughness of NiTip / Al-based composite materials. NiTip is combined with pure aluminum powder to form micron grains (d1) with a small size of <5μm; NiTip is combined with aluminum alloy powder to form micron grains (d2) of 5 to 20μm; unmilled pure aluminum powder forms micron crystals with a large size of >20μm (d3), thereby forming high-density hard areas of reinforced phase particles and tough areas without reinforced phase particles with different grain sizes in the aluminum matrix. The hard area will carry lower plastic strain, and the tough area will bear higher plastic strain. However, due to the difference in strength in space, there will be great strain incompatibility between these soft and hard units during material deformation. In this way, geometrically necessary dislocations are generated to coordinate the interface strain gradient, and heterogeneous plastic deformation based on geometrically necessary dislocations causes additional strain hardening and additional strengthening, thereby achieving the purpose of improving the strength and toughness of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a SEM image of the NiTip+pure Al composite powder obtained in step S1 of Example 1;

[0027] Figure 2 This is a SEM image of the NiTip+2024Al alloy composite powder obtained in step S2 of Example 1;

[0028] Figure 3 This is a SEM image of the NiTip / Al-based composite material obtained in Example 1;

[0029] Figure 4 This is the EDS image of the NiTip / Al-based composite material obtained in Example 1;

[0030] Figure 5 EBSD image of the NiTip / Al-based composite material obtained in Example 1;

[0031] Figure 6 This is a grain statistics diagram of the NiTip / Al-based composite material obtained in Example 1;

[0032] Figure 7 The room temperature tensile stress-strain curves of the NiTip / Al-based composite materials obtained in Example 1 and Comparative Examples 1-2 are shown. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0034] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0035] Example 1: The preparation method of the NiTi / Al-based composite material with a dual isomerization structure in this example is carried out according to the following steps:

[0036] S1: 12.48 g of NiTip (Ni:Ti atomic ratio = 50.82:49.18, average diameter ~16.10 μm) and 47.52 g of spherical aluminum powder (purity 99.9%, average diameter ~72.48 μm) were added to a planetary ball mill and mixed at 350 rpm for 10 h with a ball-to-material ratio of 15:1 to obtain a NiTip-Al mixed powder;

[0037] S2: 12.22 g of NiTip (Ni:Ti atomic ratio = 50.82:49.18, average diameter ~16.10 μm) and 47.78 g of spherical 2024 aluminum alloy powder (purity 99.9%, average diameter ~72.48 μm) were added to a planetary ball mill and mixed at 350 rpm for 10 h with a ball-to-material ratio of 15:1 to obtain a NiTip-2024Al mixed powder;

[0038] S3: 24g of NiTip-Al mixed powder, 24g of NiTip-2024Al mixed powder and 12g of unmilled aluminum powder (purity 99.9%, average diameter ~72.48μm) are stacked and packaged in a mold, and then the entire mold is placed in a discharge plasma sintering furnace and evacuated to avoid powder oxidation contamination caused by contact with air, and discharge plasma sintering is performed. The selected sintering temperature is 530℃, the uniaxial pressure is 50MPa, and the selected insulation time is 10min. After sintering is completed, the furnace is cooled and the mold is placed in a ring furnace. From top to bottom, the mold contains an extrusion cup, a pure aluminum block, a sintered composite material and a graphite gasket. Low-temperature hot extrusion is performed, and the selected hot extrusion temperature is 430℃, the insulation time is 1.5h, and the extrusion ratio is 25:1; the extrusion rate is 0.5mm / s, and a NiTi / Al-based composite material with a dual heterogeneous structure is obtained.

[0039] After testing, the NiTi / Al-based composite material with a dual isomeric structure obtained in Example 1 has a tensile strength of 363 MPa and an elongation of 6.7%.

[0040] Comparative Example 1: The preparation method of the NiTi / Al-based composite material of this embodiment is carried out according to the following steps:

[0041] S1: 12.48 g of NiTip (Ni:Ti atomic ratio = 50.82:49.18, average diameter ~16.10 μm) and 47.52 g of spherical aluminum powder (purity 99.9%, average diameter ~72.48 μm) were added to a planetary ball mill and mixed at 350 rpm for 10 h with a ball-to-material ratio of 15:1 to obtain a NiTip-Al mixed powder;

[0042] S2: 12.22 g of NiTip (Ni:Ti atomic ratio = 50.82:49.18, average diameter ~16.10 μm) and 47.78 g of spherical 2024 aluminum alloy powder (purity 99.9%, average diameter ~72.48 μm) were added to a planetary ball mill and mixed at 350 rpm for 10 h with a ball-to-material ratio of 15:1 to obtain a NiTip-2024Al mixed powder;

[0043] S3: 21g of NiTip-Al mixed powder, 21g of NiTip-2024Al mixed powder and 18g of unmilled aluminum powder (purity 99.9%, average diameter ~72.48μm) are stacked and packaged in a mold, and then the entire mold is placed in a discharge plasma sintering furnace and evacuated to avoid powder oxidation contamination caused by contact with air, and discharge plasma sintering is performed. The selected sintering temperature is 530℃, the uniaxial pressure is 50MPa, and the selected insulation time is 10min. After sintering is completed, the furnace is cooled and the mold is placed in a ring furnace. From top to bottom, the mold contains an extrusion cup, a pure aluminum block, a sintered composite material and a graphite gasket. Low-temperature hot extrusion is performed, and the selected hot extrusion temperature is 430℃, the insulation time is 1.5h, and the extrusion ratio is 25:1; the extrusion rate is 0.5mm / s to obtain a NiTi / Al-based composite material.

[0044] After testing, the NiTi / Al-based composite material obtained in Comparative Example 1 had a tensile strength of 342 MPa and an elongation of 12.4%.

[0045] Comparative Example 2: The preparation method of the NiTi / Al-based composite material of this embodiment is carried out according to the following steps:

[0046] S1: 12.48 g of NiTip (Ni:Ti atomic ratio = 50.82:49.18, average diameter ~16.10 μm) and 47.52 g of spherical aluminum powder (purity 99.9%, average diameter ~72.48 μm) were added to a planetary ball mill and mixed at 350 rpm for 10 h with a ball-to-material ratio of 15:1 to obtain a NiTip-Al mixed powder;

[0047] S2: 12.22 g of NiTip (Ni:Ti atomic ratio = 50.82:49.18, average diameter ~16.10 μm) and 47.78 g of spherical 2024 aluminum alloy powder (purity 99.9%, average diameter ~72.48 μm) were added to a planetary ball mill and mixed at 350 rpm for 10 h with a ball-to-material ratio of 15:1 to obtain a NiTip-2024Al mixed powder;

[0048] S3: 27g of NiTip-Al mixed powder, 27g of NiTip-2024Al mixed powder and 6g of unmilled aluminum powder (purity 99.9%, average diameter ~72.48μm) are stacked and packaged in a mold, and then the entire mold is placed in a discharge plasma sintering furnace and evacuated to avoid powder oxidation contamination caused by contact with air, and discharge plasma sintering is performed. The selected sintering temperature is 530℃, the uniaxial pressure is 50MPa, and the selected insulation time is 10min. After sintering is completed, the furnace is cooled and the mold is placed in a ring furnace. From top to bottom, the mold contains an extrusion cup, a pure aluminum block, a sintered composite material and a graphite gasket. Low-temperature hot extrusion is performed, and the selected hot extrusion temperature is 430℃, the insulation time is 1.5h, and the extrusion ratio is 25:1; the extrusion rate is 0.5mm / s to obtain a NiTi / Al-based composite material.

[0049] After testing, the NiTi / Al-based composite material obtained in Comparative Example 2 had a tensile strength of 384 MPa and an elongation of 5.4%.

[0050] Figure 1 The morphology of the NiTip-Al mixed powder obtained in step S1 of Example 1 is shown in FIG. Figure 1 It can be seen that, consistent with the typical morphological changes of metal powders during ball milling, pure aluminum has better deformation ability than NiTip. The nearly spherical pure aluminum is pressed into thin aluminum sheets, which are evenly dispersed without obvious stacking. NiTip changes from a spherical shape to an oblate spherical shape, and at this ball milling energy, NiTip is evenly distributed. The ideal mixing effect is achieved evenly during the ball milling process.

[0051] Figure 2 The morphology of the NiTip-2024Al mixed powder obtained in step S2 of Example 1 is shown in FIG. Figure 2 It can be seen that since 2024Al powder is harder than pure aluminum, when the same ball milling process is used, NiTi powder is greatly deformed and becomes oblate. With the increase of ball milling speed and time, 2024Al powder gradually changes from spherical to ellipsoidal. Compared with NiTip-Al mixed powder, the flakes of 2024Al powder are thicker and have a smaller radial length, and NiTip has a larger deformation.

[0052] Figure 3 The morphology of the NiTi / Al-based composite material with a dual isomeric structure obtained in Example 1 is as follows: Figure 3 It can be seen that, firstly, the SPS low-temperature sintering + low-temperature hot extrusion preparation method is adopted to achieve the uniform distribution of NiTip in the two layers (Al-NiTip, 2024Al-NiTip) ( Figure 4); secondly, due to the low sintering temperature and hot extrusion temperature, no intermetallic compounds were found at the NiTip / Al and NiTip / 2024Al interfaces in the composites, which resulted in a good metallurgical bond between the NiTip and the Al matrix in the composites; finally, due to the different particle deformation of NiTip during ball milling with different matrices, it can be clearly seen in the composites.

[0053] Figure 5 and Figure 6 The EDSD image and grain statistics of the NiTi / Al-based composite material with a dual isomerization structure obtained in Example 1 clearly show that the grain distribution has obvious trimodal grain characteristics and a layered structure. The Al-NiTip area, 2024Al-NiTip area, and Al area are streamlined along the extrusion direction. The NiTip in the 2024Al-NiTip area is more deformed than that in the Al-NiTip area, and is distributed in a long strip shape. The grains in the Al-NiTip area are obviously refined, with an average grain size of 2.61 μm ( Figure 6 ); 2024Al-NiTip forms larger micron-sized grains with an average grain size of 11.62μm; the unmilled Al powder forms large micron-sized crystals with an average grain size of 22.82μm.

[0054] Figure 7 The room temperature tensile test results of the NiTi / Al-based composite material with a dual isomerization structure obtained in Example 1 are as follows: Figure 7 It can be seen that the yield strength of the dual heterogeneous structure NiTi / Al-based composite material of Example 1 is 178.9MPa, the tensile strength is 363MPa, and the elongation is 6.7%. The dual-configuration structure shows better strain hardening and strength-ductility synergy. The layered configuration improves the mechanical properties of the composite material in parallel to the stacking direction. It plays an additional back stress strengthening role. This shows the great potential of dual heterogeneous structure composite materials in achieving the goal of strengthening and toughening aluminum-based composite materials.

[0055] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a NiTi / Al-based composite material having a dual isomerization structure, characterized in that: The method: S1: Mix NiTip and pure aluminum powder by high-energy ball milling to obtain NiTip-Al mixed powder; S2: mixing NiTip and aluminum alloy powder by high-energy ball milling to obtain NiTip-Al alloy mixed powder; S3: NiTip-Al mixed powder, NiTip-Al alloy mixed powder and unmilled aluminum powder are stacked and packaged in a mold, and low-temperature discharge plasma sintering is performed under vacuum conditions, followed by low-temperature hot extrusion to obtain a NiTi / Al-based composite material with a dual heterogeneous structure.

2. The method according to claim 1, characterized in that The amount of NiTip added in S1 is 11-50wt.% of pure aluminum powder, the high-energy ball milling speed is 300-450rpm, the time is 8-15h, and the particle size of the NiTip-Al mixed powder is <5μm.

3. The method according to claim 1, characterized in that The amount of NiTip added in S2 is 11-50wt.% of the aluminum alloy powder, the high-energy ball milling speed is 300-450rpm, the time is 8-15h, and the particle size of the NiTip-Al alloy mixed powder is 5-20μm.

4. The method according to claim 1, characterized in that: The mass ratio of NiTip-Al mixed powder, NiTip-Al alloy mixed powder and unmilled aluminum powder in S3 is (1.5-2.5): (1.5-2.5): 1, and the particle size of the unmilled aluminum powder is 50-150 μm.

5. The method according to claim 1, characterized in that The temperature of low-temperature discharge plasma sintering in S3 is 500-530°C, the pressure is 40-60MPa, and the time is 5-15min.

6. The method according to claim 1, characterized in that In S3, the hot extrusion temperature is 400-430°C, the extrusion ratio is (16-25):1, and the extrusion rate is 0.1-0.5 mm / s.

7. The high-strength and tough NiTi / Al-based composite material prepared by the method according to any one of claims 1 to 6, characterized in that: The composite material has a tensile strength of ≥360 GPa and an elongation of ≥6.7%.

8. Application of the high-strength and tough NiTi / Al-based composite material according to claim 7 in the fields of aerospace and automotive engineering.

9. Use of the method according to any one of claims 1 to 6 in preparing NiTi / metal matrix composite materials.

10. The use according to claim 9, characterized in that: The metal matrix is ​​one of Mg, Fe, Ti, Cu and their alloys.

Citation Information

Patent Citations

  • Composite material with in-situ synthesized particles and preparation method of composite material

    CN112176212A

  • Bricking-like bionic composite prepared ceramic reinforced aluminum matrix composite

    CN113234952A

  • Preparation method of graphene and silicon carbide hybrid reinforced aluminum-based composite material

    CN114951664A

  • Preparation method of layered distribution ceramic reinforced aluminum composite material

    CN115679141A

  • Multi-grain-size layered Al-Ti composite material and preparation method thereof

    CN117983817A